The geochemistry of fossil termite nests in Calitzdorp, Western Cape, South Africa - Jacobs, Rabia (Department of Geological Sciences, 2025)
Termites alter soil profiles by gathering nutrient-rich materials to construct their nests, known as termitaria. Certain termite species also fortify their termitaria using a combination of saliva and excrement (frass), resulting in geochemically distinct termitaria relative to the host soils. The enrichment of exchangeable bases derived from organic matter, including termite frass, and upward groundwater movement frequently leads to post-construction carbonate precipitation within termitaria. Fossil termitaria near Calitzdorp, Western Cape, South Africa, were described nearly two decades ago, but no detailed work has been performed on them until now. Here, these calcretised Quaternary features, which are largely composed of calcite and dolomite, are investigated to 1) determine whether there is evidence of nutrient mining or preferential nutrient enrichment in the fossil termitaria compared to their host palaeosols and 2) assess the palaeoenvironmental conditions at the time of carbonate precipitation. The fossil termitaria are distinct from their host palaeosols, being enriched in CaO, MgO, MnO, and P₂O₅ and depleted in Al₂O₃, Cu, Fe₂O₃, K₂O, and Zn, suggesting that the termites enriched their termitaria by depositing organic matter. However, there is no evidence of termites selectively mining materials, as observed in modern termitaria. The termitaria's unique geochemical signature is attributed to post-construction carbonate precipitation facilitated by termite activity. The enrichment of CaO and MgO can be linked to the termites' localised deposition of organic matter, rich in exchangeable base cations (Ca²⁺, Mg²⁺, K⁺, Na⁺). While calcite is present in other termitaria, the dolomite found in the termitaria in this study is distinctive and likely resulted from secondary carbonate precipitation aided by magnesium-rich organic matter. This exchangeable base enrichment, enhanced by termite activity, likely led to the preferential calcretisation of the termitaria, setting them apart from their host palaeosols. The pedogenic carbonate within the termitaria and some palaeosols indicates an arid environment at the time of carbonate formation. The δ¹³C values of the termitaria range from 0 to -8‰, indicating a mixed C₃-C₄ vegetation matrix, with a more pronounced C₄ signature at the northern ichnosite and a stronger C3 signature in the southern ichnosite. This mixture suggests a close association with year-round rainfall, with a higher proportion of arid-adapted vegetation in the north and a lower proportion in the south. Furthermore, the δ¹⁸O values indicate a similar water source between the two ichnosites and reflect palaeotemperatures ranging from ~20 to 35 °C.